APLIKASI EKSTRAK BAWANG MERAH DAN KECAMBAH KACANG HIJAU UNTUK INVIGORASI BENIH CABAI RAWIT (Capsicum frutescens L.) KADALUARSA - Nafila Alifia Azka (Agrotechnology Innovation Center, Universitas Gadjah Mada, Yogyakarta, 2021)
Capsicum frutescens L. is one of the most important horticultural commodities in Indonesia. One of the obstacles that are often faced by farmers in chili cultivation is the low ability of chili seeds to germinate because of the seed deterioration during the storage period. The low ability of seed germination can be solved by using organic priming treatment. In this study, the invigoration of expired chili seeds was carried out using organic priming of shallots extract, mungbean sprouts extract, onions + mungbean sprouts extract, and water as a control treatment. Based on the results of the study, organic priming of expired chili seeds using onion extract and a mixture of onion + mungbean sprouts was able to increase seed germination, but the treatment using mungbean sprouts extract had lower seed germination than the control treatment. Organic priming had no significant effect on the vigor index of expired chili seeds. Shallots extract was the most optimal organic priming for invigorating expired chili seeds.